Criminalization of Perpetrators of Terrorism: A Criminal Law and National Security Approach - Jesslyn Elisandra Harefa; Yasmirah Mandasari Saragih; Fauzan Fauzan; Bonari Tua Silalahi; Ireny Natalia Putri Sihite (Journal of Strafvordering Indonesian, 2024)
The crime of terrorism is a serious threat that can undermine the political, social, and economic stability of a country, especially in Indonesia. Its handling involves various approaches, including criminal law and national security policy. Law No. 5/2018 is the main legal basis in eradicating terrorism, providing broad authority for law enforcement officials in taking action against perpetrators. This research aims to evaluate the application of criminal law and national security approach in combating terrorism in Indonesia. A juridical-normative approach is used in analyzing data obtained through interviews with law enforcement officers, BNPT officials, and legal experts, as well as the study of related literature. The results show that although law enforcement against terrorism perpetrators in Indonesia has been implemented with severe criminal sanctions, the main challenge lies in the rehabilitation and deradicalization of perpetrators. Non-optimal deradicalization program has the potential to fail in reducing potential long-term threats. In addition, monitoring the funding of terrorism and the use of digital technology are important elements in prevention. Therefore, law enforcement must be carried out with due regard to human rights principles, involving collaboration between various institutions as well as educational and religious-based approaches. Success in combating terrorism requires a comprehensive strategy and good coordination between the government, society, and international institutions..